MO690HIGHER EXPRESSION OF TOLL LIKE RECEPTOR AND CELL ADHESION MOLECULES ARE ASSOCIATED WITH RECURRENT/RELAPSE PERITONITIS AND MORTALITY IN PATIENT ON CAPD. (29th May 2021) - Prasad, Narayan; Fatima, Nida; Singh, Mantabya; Sahu, Chinmoy
Abstract: Background and Aims: CAPD is an established modality of treatment for patients with end stage renal disease (ESRD). Peritonitis is a leading cause of technique failure and death in patients on CAPD. Studies on expressions of host genetic factors like TLRs, CAMs, Pro and Anti-inflammatory cytokines and their link to peritonitis and other co-morbidity and functional status are lacking throughout the world. Hence the present study was done to determine the expressions of TLR2 and TLR4, CAMs and inflammatory cytokines in patients on CAPD. Method: A total of 110 ESRD patients categorized into 3 groups: 1- CAPD patients (n=45), group 2- CAPD with peritonitis patients (n=35), and group 3- CAPD patients with recurrent/relapsing peritonitis. (n=30) from department of Nephrology, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Raebareli Road, Lucknow were included in the study. Blood sample was collected for analysis of cytokines and Cell adhesion molecules level and RNA extraction. Dialysate (only from patients undergoing PD with or without peritonitis)- whole drained bag; 50-100 ml for microscopy and culture for bacterial and fungal pathogens using automated BACTEC culture system in patients with peritonitis and supernatant was collected for cytokine ELISA. Statistical analysis: One-way ANOVA (Two tailed) and non-parametric student t-test used for statistical analysis of differences between the group. Results: mRNA expression of TLR 2 and TLR 4 expression was higher in peritonitis and recurrent/relapsing peritonitis group as compared to CAPD patient without peritonitis group. mRNA expression of TNF-alpha, IL-1B and IFN-gamma was higher in peritonitis group of patients compared to all other group of patients. mRNA expression of IL-10 and IL-4 was also highest in Peritonitis group. Level of IL-1β and TNF-alpha was observed to be elevated in peritonitis and recurrent/relapse peritonitis patients compared to CAPD in sera and dialysate. IL-12 level in Sera was also elevated in peritonitis patients but its level in dialysate was highest in CAPD without peritonitis as compared to peritonitis and recurrent/relapse. IL-10 and IL-4 was observed to be elevated in peritonitis group followed by CAPD with recurrent/relapse peritonitis in sera whereas in dialysate level of IL-4 was higher in both peritonitis group and Recurrent groups of patients but IL-10 level was highest in peritonitis group but less in recurrent/relapse. mRNA Expression levels of adhesion molecule ICAM-1 and LFA-1 were observed to be higher in Peritonitis and Recurrent groups as compared to the CAPD without peritonitis; whereas, in sera the level of ICAM-1 was higher in peritonitis patients. However, in dialysate its level was observed to be almost similar. Level of LFA-1 was observed to be higher in peritonitis group in dialysate but in sera its level was higher in Recurrent group with peritonitis. Conclusion: It is likely that CAMs are also involved in the pathogenesis of CAPD peritonitis, its morbidity and mortality. TLRs activation by bacterial molecules leads to the induction of chemokines and cytokines through the activation of NF-ķB pathway and may be responsible for atherosclerosis, morbidity, and mortality in ESRD patients. Elevated level of ICAM-1, IL-1beta, TNF-a and IFN-G may be responsible for chronic inflammation in PD patients.